New solid phase of dipolar systems - Levesque, D. (Condensed Matter Physics, 2017)
The systems of molecules with a permanent dipole moment have solid phases with various crystal symmetries. In particular, the solid phases of the simplest of these systems, the dipolar hard sphere model, have been extensively studied in the literature. The article presents Monte Carlo simulation results which, at low temperature, point to the stability of a polarized solid phase of dipolar hard spheres with the unusual number of eleven nearest neighbors, the so-called primitive tetragonal packing or tetragonal close packing. Системи молекул з постiйним дипольним моментом мають твердi фази з кристалами рiзної симетрiї. Зокрема, твердi фази найпростiшої з таких систем, моделi дипольних твердих сфер, широко вивченi у лiтературi. В статтi представленi результати моделювання методом Монте-Карло, якi при низькiй температурi вказують на стабiльнiсть поляризованої твердої фази дипольних твердих сфер з незвичайним числом одинадцяти найближчих сусiдiв, так званої примiтивної тетрагональної упаковки або тетрагональної закритої упаковки.